PENGARUH JENIS MULSA TERHADAP PERTUMBUHAN DAN HASIL BAWANG MERAH (Allium ascalonicum Var. Lembah Palu) YANG DIBERI SUNGKUP - Wisudawati, Muhammad Anshar, Iskandar Lapanjang, Diakh (AGROTEKBIS, 2016)
This research aims to determine the effect of various types of mulch on the growth and yield components of shallot varieties Lembah Palu were are given the containment. This research was conducted at the Hall Horticulture Seed Napu Watumaeta Village, Poso district, Central Sulawesi Province. The timing of the research in the May-July 2015. This study uses a randomized block design one factor. The treatments tested were four types of mulch that is without mulch, rice straw mulch, black plastic mulch and silver plastic mulch, each treatment was repeated three times so that there are 4 x 3 = 12 units of a plot. Data processed by analysis of variance and differences Â among the treatments were tested were determined by LSD 5%. The results showed that rice straw mulch and silver plastic mulch resulted in the highest increase plant height and length of the longest leaf at the age of 50 days after planting. Black plastic mulch, and silver plastic mulch and without mulch produce the largest bulbs convolution results.